Antroponimy i toponimy w łużyckich tłumaczeniach Ewangelii według św. Mateusza - Waliszewska, Joanna (Slavia Occidentalis, 2016)
The article is devoted to the analysis and description of anthroponyms and toponyms occurring in Catholic Upper-Sorbian translations of The Gospel According to St. Matthew. The excerpted forms have been compared with one another as well as with the forms encountered in various translations: the Protestant Upper-Sorbian, the Czech, the German (Catholic and Protestant). The study is composed of the historical outline of the Sorbian translations of the Bible and the analysis of different linguistic manifestations of proper names in the Catholic editions of The Gospel According to St. Matthew.